2002
DOI: 10.1590/s0034-89102002000100008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de alcoolemia em vítimas de causas externas admitidas em centro urbano de atenção ao trauma

Abstract: OBJETIVOS: Estudar a freqüência de alcoolemia positiva em vítimas de causas externas e caracterizar a freqüência do uso dessa substância nos diferentes tipos de causas externas. MÉTODOS: Estudo de prevalência de alcoolemia em pacientes admitidos em um centro de atenção ao trauma, no município de São Paulo, SP, Brasil. Os pacientes foram selecionados aleatoriamente no decorrer de um ano (agosto de 1998 a agosto de 1999). Os procedimentos consistiram em coleta de sangue para dosagem alcoólica e aplicação de ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
2
25

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 5 publications
5
17
2
25
Order By: Relevance
“…The analysis of data concerning more than 65,000 individuals aged 20 years or more in relation to the study of victims of accidents and violence in 2006 and 2007 24 shows that the report of previous intake of alcohol was significantly higher (p<0.001) among individuals younger than 40 years old (17.6%) than among those aged 40 years or more (12.0%). This situation is similar to that observed in 1998 and 1999 by Gazal-Carvalho et al 25 in the city of São Paulo. In Russia, a casecontrol study involving almost 50,000 deaths showed a risk approximately 6 times higher of deaths by accidents and violence in the group that presented high alcohol consumption, besides the risk for other diseases, especially chronic 26 .…”
Section: * Percentual Ajustado Para Representar a População Adulta Tosupporting
confidence: 92%
“…The analysis of data concerning more than 65,000 individuals aged 20 years or more in relation to the study of victims of accidents and violence in 2006 and 2007 24 shows that the report of previous intake of alcohol was significantly higher (p<0.001) among individuals younger than 40 years old (17.6%) than among those aged 40 years or more (12.0%). This situation is similar to that observed in 1998 and 1999 by Gazal-Carvalho et al 25 in the city of São Paulo. In Russia, a casecontrol study involving almost 50,000 deaths showed a risk approximately 6 times higher of deaths by accidents and violence in the group that presented high alcohol consumption, besides the risk for other diseases, especially chronic 26 .…”
Section: * Percentual Ajustado Para Representar a População Adulta Tosupporting
confidence: 92%
“…Research conducted in São Paulo-SP 24 has shown that 28.9% of the victims of external causes presented positive blood alcohol levels. International literature indicates frequencies of 6.0% to 34.0% of positive blood alcohol levels amongst nonfatal victims of different external causes admitted to emergency services 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Essa variação é esperada, visto que há diferenças entre os serviços, públicos ou não, e sua localidade, bem como entre as características sociodemográficas, culturais e políticas das populações admitidas 22 . Quanto ao perfil dos pacientes que apresentaram maiores prevalências de consumo de risco de álcool, também é semelhante aos estudos nacionais e internacionais, ou seja, é encontrado em períodos noturnos, fins de semana, do sexo masculino, solteiros, na faixa etária entre 18 e 46 anos 2,3,[10][11][12][13][14][15][16] . Nesse sentido, o PS apresenta-se como um importante espaço de identificação de usuários abusivos de álcool.…”
Section: Discussionunclassified
“…A comparação desses dados com os de outros países mostra que as taxas brasileiras são muito altas -terceiro lugar para os homicídios e quinto lugar para os acidentes de trân-sito -e que o consumo de álcool tem uma participação significativa nessas ocorrências 29 . Nesse sentido, esse estudo reforça as evidências de que o uso de bebidas alcoólicas figura-se como um dos problemas de saúde no Brasil [1][2][3][4][5][6][7][8][9][10][11]30 .…”
Section: Discussionunclassified
See 1 more Smart Citation